Game of stars - DasGupta, Sayantani (DasGupta, Sayantani. Kiranmala and the kingdom beyond, 2020)
The Demon Queen shows up in twelve-year-old Kiranmala's bedroom but can't seem to get her message across to Kiranmala. Then, over an interdimensional television station, Kiran learns her homeland is in chaos and her friends are in danger. She once again travels to the Kingdom Beyond and faces additional threats from her evil Serpent King father, all while trying to determine who her true friends are.